Penerapan Prinsip 5C Pada Resiko Pembiayaan Murabahah Di BMT Istiqomah Tulungagung dan BMT Pahlawan Tulungagung - Dwi Wahyu Ningtyas (Universitas Muhammadiyah Ponorogo, 2022)
This research is motivated by the development of Islamic microfinance institutions called Baitul Maal wat Tamwil. The 5C principle in BMT Istiqomah and BMT Pahlawan are used to anticipate the risk of problematic financing in the future. The problems that often occur in BMT Istiqomah and BMT Pahlawan are almost similar, namely the character of members or prospective members who are not honest. Based on this background, researchers are interested in conducting research with the title